Perancangan Antarmuka Sistem Informasi Wajib Lapor di BAPAS Kelas I Palembang - Rizky Amalia; Evi Fadilah (Ikatan Ahli Informatika Indonesia, 2025)
Efficiency and accuracy in the mandatory reporting process for correctional clients present significant challenges for BAPAS Class I Palembang. This study aims to design a mobile-based mandatory reporting information system that supports the activities of both clients and Correctional Officers (PK). The previously manual reporting process caused several issues, including low client discipline, difficulties for PK in monitoring client progress, and risks of data loss or inaccuracy. The method applied is User Centered Design (UCD), which includes stages of understanding the context of use, specifying user requirements, designing solutions using Figma, and evaluating the design with the System Usability Scale (SUS) method. Data were collected through observation, stakeholder interviews, and usability testing by respondents. The results indicate that the designed application meets user needs and is easy to use, with an average SUS score of 82, falling into the Excellent category.